Antimicrobial Resistance and Biofilms Underlying Catheter-Related Bloodstream Coinfection by Enterobacter cloacae Complex and Candida parapsilosis - Štefánek, Matúš (2022)
Biofilm-associated infections are a public health concern especially in the context of healthcare-associated infections such as catheter-related bloodstream infections (CRBSIs). We evaluated the biofilm formation and antimicrobials resistance (AMR) of Enterobacter cloacae complex and Candida parapsilosis co-isolated from a CRBSI patient. Antimicrobial susceptibility of central venous catheters (CVCs) and hemoculture (HC) isolates was evaluated, including whole genome sequencing (WGS) resistome analysis and evaluation of gene expression to obtain insight into their AMR determinants. Crystal violet assay was used to assess dual biofilm biomass and microscopy was used to elucidate a microorganism’s distribution within biofilms assembled on different materials. Bacteria were multidrug-resistant including resistance to colistin and beta-lactams, likely linked to the mcr-9-like phosphoethanolamine transferase and to an ACT family cephalosporin-hydrolyzing class C beta-lactamase, respectively. The R398I and Y132F mutations in the ERG11 gene and its differential expression might account for C. parapsilosis resistance to fluconazole. The phenotype of dual biofilms assembled on glass, polystyrene and polyurethane depends on the material and how biofilms were initiated by one or both pathogens. Biofilms assembled on polyurethane were denser and richer in the extracellular polymeric matrix, and microorganisms were differently distributed on the inner/outer surface of the CVC.